Multiscale model of regional population decline in little brown bats due to white‐nose syndrome. Issue 15 (4th July 2019) - Kramer, Andrew M.; Teitelbaum, Claire S.; Griffin, Ashton; Drake, John M.
Abstract: The introduced fungal pathogen Pseudogymnoascus destructans is causing decline of several species of bats in North America, with some even at risk of extinction or extirpation. The severity of the epidemic of white‐nose syndrome caused by P. destructans has prompted investigation of the transmission and virulence of infection at multiple scales, but linking these scales is necessary to quantify the mechanisms of transmission and assess population‐scale declines. We built a model connecting within‐hibernaculum disease dynamics of little brown bats to regional‐scale dispersal, reproduction, and disease spread, including multiple plausible mechanisms of transmission. We parameterized the model using the approach of plausible parameter sets, by comparing stochastic simulation results to statistical probes from empirical data on within‐hibernaculum prevalence and survival, as well as among‐hibernacula spread across a region. Our results are consistent with frequency‐dependent transmission between bats, support an important role of environmental transmission, and show very little effect of dispersal among colonies on metapopulation survival. The results help identify the influential parameters and largest sources of uncertainty. The model also offers a generalizable method to assess hypotheses about hibernaculum‐to‐hibernaculum transmission and to identify gaps in knowledge about key processes, and could be expanded to include additional mechanisms or bat species. Abstract : Forecasting declines in North American cave‐dwelling bats due to white‐nose syndrome requires linking within‐cave disease processes to between‐cave dispersal and fungal spread. We use a model linking these scales to look at plausible scenarios for population dynamics. We constrain the parameter space consistent with observed spread and find little impact of either variation in philopatry or cave‐level disease severity on population declines.